Mengembangkan Kemampuan Motorik Kasar Melalui Permainan Boba (Bola Basket) Modifikasi Pada Anak Kelompok B TK Kusuma Mulia Sugihwaras Kecamatan Purwoasri Kabupaten Kediri - Istifadah, Husna; Iswantiningtyas, Veny; Nugroho, Isfauzi Hadi (Universitas Nusantara PGRI Kediri, 2024)
This research aims to develop the gross motor skills of KM Sugihwaras Kindergarten children 5-6 years with a modified game of Boba (basketball). This research used three cycles of classroom action research. The subjects were 28 children in group B of kusuma mulya Sugihwaras Kindergarten. The object of the research is gross motor skills through modified Boba (basketball) games for children. Three cycles of classroom action research were used in the research method. Based on research findings, the modified boba (basketball) game was able to developchildren's gross motor skills pre-cycle by an average of 17.8%, cycle I by 21.4%, and in cycle II by the same amount, based on research findings. average 53.57%, while cycle 3 average 89.2%. Based on these findings, the modified Boba (basketball) game succeeded in increasing the percentage of AUD learning outcomes.